Micelle bound structure and model membrane interaction studies of the peptide Hylin a1 from the arboreal south American frog Hypsiboas albopunctatus - Alves, Eliane S.F.; Junior, Edson C. [UNESP]; Cilli, Eduardo M. [UNESP]; Castro, Mariana S.; Fontes, Wagner; De Magalhães, Mariana T.Q.; Lião, Luciano M.; De Oliveira, Aline L. (Bentham Science Publishers, 2015)
Antimicrobial peptides (AMPs) appear as a promising therapeutic candidate against multiresistant pathogens, because they are able to kill microorganisms and have low toxicity of resistance cells. Hylin a1 (Hy-a1, IFGAILPLALGALKNLIK-NH2) is a peptide extracted from the skin secretion of the frog Hypsiboas albopunctatus, which displays antimicrobial and hemolytic activities. We report here structural studies of Hy-a1 using different techniques such as fluorescence, CD and NMR. Our data showed that Hy-a1 acquires a well defined amphipathic β-helix when interacting with a membrane-like environment. Furthermore, Hy-a1 presented different affinity when compared to membranes of zwitterionic or anionic lipid composition. Finally, we proposed a molecular interaction model of this peptide with micelles.
Keywords: Amphipathic; Antimicrobial peptide; Frog skin secretion; Hemolytic; Hylin a1; NMR; Pore formation; Structure